Research Papers : Genetic basis of stripe rust resistance in transgressive derivatives of a cross between susceptible bread wheat parents - Singh, Rupinder Pal; Srivastava, Puja; Sharma, Achla; Bains, N. S. (The Indian Journal of Genetics and Plant Breeding, 2017)
Parental lines, F1s, F2 populations as well as F3 and F4 families and F6, F7 RILs from bread wheat cross PBW 621 x HD 2967 were evaluated for stripe rust resistance against a highly virulent pathotype in experiments spanning six crop seasons. HD2967, the widely cultivated wheat variety in North Western Plains of India and PBW 621 have shown successively lowered levels of stripe rust resistance over the years. F1 of these parents showed lack of dominance. The segregation pattern for stripe rust resistance in F2, F3 and F4 showed transgressiveness for resistance. Chi-square analysis indicated that resistant segregants possess two genes, one contributed by PBW 621 and the other by HD 2967. These results were confirmed over two years using F6 and F7 RILs. Possible genetic mechanisms for this residual resistance and implications for breeding programme are discussed.